Gay is OK! a Christian perspective - Ngeo, Boon Lin (Gerakbudaya Enterprise, 2013)
Is it right for Christians to condemn homosexuality? Is it possible to be gay and Christian? Is gay Christian an oxymoron? In this book, Gay Is OK!: A Christian Perspective, the author as a Christian theologian and a pastor provides a concise and yet profound analysis, as well as alternative scriptural interpretations of historical criticism of the story of Sodom in Genesis 19, Leviticus 18:22; 20:13, Romans 1:26-27, 1 Corinthians 6:9-10, and 1 Timothy 1:9-10. According to the author, these are the biblical verses which have been wrongly employed and misused by many Christians to condemn gays and lesbians, and argues forcefully that gay is ok and that Christian churches should embrace LGBT people. The major objective of this book is to look at what the biblical authors were really rejecting by scrutinizing the historical contexts in which the biblical texts were written. The author also believes in the separation of religion and state, he argues for it in the first part of this book and asserts that even if Christianity were to condemn homosexuality, no one, including Christians, should make any laws to discriminate against gay people due to religious reasons.